Characterization of a new sustainable supramolecular solvent and application to the determination of oxy-PAHs in meat, seafood and fish tissues. (30th March 2023) - Jesús Dueñas-Mas, María; Ballesteros-Gómez, Ana; Rubio, Soledad
Graphical abstract: Highlights: New green SUPRAS made up fatty alcohols, water and 2-MeTHF are characterized. They were successfully applied to the extraction of oxy-PAHs from food. The method was simple and with low consumption of solvent (200 µL SUPRAS). Meat, fish and seafood samples were contaminated with oxy-PAHs (n.d. − 8 ng/g). Abstract: In this study we develop a green treatment method based on supramolecular solvents (SUPRASs) made up of reverse aggregates of short/medium chain length alcohols (C6 -C10 ) in mixtures of water and a sustainable organic solvent (methyl-tetrahydrofuran). SUPRASs ingredients have low toxicity and can be obtained from renewable sources. The new SUPRASs were characterized and its suitability for determination of oxygenated polycyclic aromatic hydrocarbons (oxy-PAHs) in food was tested. Analysis was made by liquid chromatography coupled to high resolution mass spectrometry. The method provided quantification limits in the range 0.4–4 ng g −1 with low consumption of reagents (200uL of SUPRAS per sample) and it was based on simple agitation and centrifugation without concentration/evaporation steps. All target compounds (except 11-H-benzo[ b ]fluoren-11-one) were found in 7 out of 19 samples, mainly in fish and seafood samples, with levels in the range n.d. – 8 ng g −1 .